2022
DOI: 10.1021/acs.langmuir.2c00317
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Microspheric Soil Conditioner Based on Chitosan-Grafted Poly(acrylamide-co-acrylic acid)/Biochar

Abstract: A multifunctional microspheric soil conditioner based on chitosan-grafted poly(acrylamide-co-acrylic acid)/biochar [CS-g-P(AM-co-AA)/BC] was prepared. First, the P(AM-co-AA) was synthesized and successfully grafted onto CS, and the three-dimensional network structure of microspheres was formed with N,N-methylenebis-(acrylamide) as the cross-linking agent according to the inverse suspension polymerization method. Meanwhile, BC and urea were encapsulated into the body of microspheres during the polymerization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Further, to confirm the conclusion that the doping of Fe 3 O 4 with CNT-NH 2 can increase the specific surface area for better adsorption performance, the sample pore characteristics were characterized through N 2 adsorption–desorption measurements (Figure G,I). It can be found that WSe 2 and Se 2 @Fe 3 O 4 @CNT-NH 2 exhibited type IV isotherms as well as type H3 hysteresis loops, which are features of mesoporous materials. The specific surface areas of WSe 2 and the flower-like WSe 2 @Fe 3 O 4 @CNT-NH 2 nanocomposite were 12.8 and 50.2 m 2 /g, respectively. The relative pore size distribution (PSD) curves showed that the majority of the pore sizes were in the ranges of 2–4 and 2–6 nm, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Further, to confirm the conclusion that the doping of Fe 3 O 4 with CNT-NH 2 can increase the specific surface area for better adsorption performance, the sample pore characteristics were characterized through N 2 adsorption–desorption measurements (Figure G,I). It can be found that WSe 2 and Se 2 @Fe 3 O 4 @CNT-NH 2 exhibited type IV isotherms as well as type H3 hysteresis loops, which are features of mesoporous materials. The specific surface areas of WSe 2 and the flower-like WSe 2 @Fe 3 O 4 @CNT-NH 2 nanocomposite were 12.8 and 50.2 m 2 /g, respectively. The relative pore size distribution (PSD) curves showed that the majority of the pore sizes were in the ranges of 2–4 and 2–6 nm, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, ZSM-5@PDA−CNT−FA can adapt to different environments to solve the acid−alkaline problems currently faced by soils and has wide applicability. To further understand the release mechanism of FA in the samples, first-order (eq 3), Higuchi (eq 4), Ritger−Peppas (eq 5), and parabolic diffusion (eq 6) models were used to fit the slow-release data of FA 48,49 M M kt ln(1 / )…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To further understand the release mechanism of FA in the samples, first-order (eq ), Higuchi (eq ), Ritger–Peppas (eq ), and parabolic diffusion (eq ) models were used to fit the slow-release data of FA , where M t / M ∞ is the fraction of urea released, k is the release rate constant, n is the diffusion index, and b is a constant.…”
Section: Resultsmentioning
confidence: 99%
“…In [ 127 ], a multifunctional microspheric soil conditioner based on chitosan-grafted poly(acrylamide- co -acrylic acid)/biochar [CS- g -P(AM- co -AA)/BC] was prepared. First, the P(AM- co -AA) was synthesized and successfully grafted onto CS, and the three-dimensional network structure of microspheres was formed with N , N -methylenebis(acrylamide) as the cross-linking agent according to the inverse suspension polymerization method.…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 99%